THE ROLE OF DYNAMIC CAPABILITY AND ORGANIZATIONAL AGILITY IN IMPROVING MSMEs' PERFORMANCE - Wahyu Islamuddin; Jeziano Rizkita Boyas; Nafia Ilhama Qurratu’aini; Devika Cherly P (LPPM STIE Muhammadiah Bandung, 2025)
Entrepreneurial dynamics encounter significant challenges in a competitive and fast-changing environment. This research aims to explore the role of dynamic capability and organizational agility in enhancing the performance of micro, small, and medium enterprises (MSMEs), particularly within the batik and embroidery sectors in Pasuruan Regency, specifically in the Bangil, Beji, Gempol, and Pandaan areas. Data was gathered from 48 MSMEs owners through questionnaires, and the analysis was performed using quantitative methods with SmartPLS 4.0 software to test the research hypotheses. The findings revealed that dynamic capability is essential for enhancing MSMEs' performance, while organizational agility also positively influences performance. Additionally, the study indicated that both dynamic capability and organizational agility positively impact the performance of batik and embroidery MSMEs in the Bangil, Beji, Gempol, and Pandaan regions. This research provides valuable insights for decision-making and strategy formulation in the face of market uncertainties, offering practical recommendations for MSMEs owners to enhance their efficiency and competitiveness.